2020
DOI: 10.3904/kjim.2020.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early anti-TNF use on clinical outcomes in Crohn’s disease: a nationwide population-based study

Abstract: Background/Aims: The optimal timing for initiation of anti-tumor necrosis factor (TNF) therapy in Crohn's disease (CD) is still debated. Little is known about the clinical outcomes of early versus late administration of anti-TNF agents, especially in Asian CD patients. We aimed to evaluate the impact of early anti-TNF therapy on clinical outcomes in Korean CD patients. Methods: Using the Korean National Health Insurance Claims database, we collected data on patients diagnosed with CD who received anti-TNF ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…Furthermore, it has been suggested that the decrease in surgical rates occurs mostly due to emergency procedures, with no significant changes in elective procedures [ 54 ]. The results from this study are in agreement with international trends, showing progressive reductions in surgeries and hospitalizations, including surgical hospitalizations, and decreased surgery-related lethality among the patients with IBD throughout the country [ 23 , 55 , 56 ]. The widespread use of immunosuppressants, followed by the introduction of biologic therapies in the public health system in the last decade, might have had an important impact on the overall outcomes of patients with IBD in the country, as pointed out previously [ 57 ].…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, it has been suggested that the decrease in surgical rates occurs mostly due to emergency procedures, with no significant changes in elective procedures [ 54 ]. The results from this study are in agreement with international trends, showing progressive reductions in surgeries and hospitalizations, including surgical hospitalizations, and decreased surgery-related lethality among the patients with IBD throughout the country [ 23 , 55 , 56 ]. The widespread use of immunosuppressants, followed by the introduction of biologic therapies in the public health system in the last decade, might have had an important impact on the overall outcomes of patients with IBD in the country, as pointed out previously [ 57 ].…”
Section: Discussionsupporting
confidence: 86%
“…Universal medical coverage was achieved in Korea in 1989, and all Koreans are mandatorily enrolled in the NHIS database. Thus, the NHIS database contains data on all claims, including prescribed drugs and procedures, for the entire population of South Korea [ 10 , 11 , 12 , 13 ]. Medical claims data submitted between 1 January 2013 and 31 December 2019, were obtained for the current study.…”
Section: Methodsmentioning
confidence: 99%
“…IFX (Remicade, Janssen, Seoul, Korea; Remsima, Celltrion, Incheon, Korea; and Remaloce, SAMSUNG BIOEPIS, Incheon, Korea) is a chimeric monoclonal antibody biologic drug that is infused intravenously at 5 mg/kg over 2 hours (shortened to 1 hour if well tolerated) at 0, 2, and 6 weeks and every 8 weeks thereafter in IBD patients ( Table 3 ) [ 81 , 82 ]. A subcutaneous formulation of the IFX biosimilars, CT-P13 (Remsima) or SB2 (Remaloce), is now available for IBD patients.…”
Section: Anti-tnf-α Agentsmentioning
confidence: 99%